Energy analysis of willow production for bioenergy in Sweden. (October 2018) - Nordborg, Maria; Berndes, Göran; Dimitriou, Ioannis; Henriksson, Annika; Mola-Yudego, Blas; Rosenqvist, Håkan
Abstract: Energy from biomass, including lignocellulosic crops such as willow ( Salix spp.), is expected to increase in importance in Sweden. This study assesses the average annual net energy yield and the ratio between gross energy yield and total primary energy input for well-managed current commercial willow production systems in Sweden subject to three levels of fertilization with mineral nitrogen (N): N-high, N-medium, and N-zero. The average annual net energy yields are estimated at 175, 133, and 86 GJ ha −1 yr −1, and the (dimensionless) energy ratios are estimated at 19, 32, and 47, for N-high, N-medium, and N-zero, respectively. Thus, there is a trade-off between achieving a high net energy yield and achieving a high energy ratio. Since the total primary energy input amounts to ≤ 5% of the gross energy yield in all cases, and the amount of arable land is limited, productivity increases may be considered more important than energy efficiency improvements. Substantial improvements in energy performance can be achieved by increasing harvest levels and improving energy efficiency in ammonia production and biomass transportation. The results should be interpreted with caution since several input parameters, especially energy use in ammonia production, fuel consumption rates, and the yield response to fertilization, are associated with considerable uncertainties. Highlights: Bioenergy can help in the transition to fossil-fuel independence. Willow production with three different levels of N fertilization are studied. Higher N fertilization means higher productivity, but lower energy efficiency. The gross energy yields are between 19 and 47 times larger than the energy inputs. There is room for improvement in the productivity and energy performance.